Importance of farming system concept in development of less favoured areas - Barbara Roszkowska-Mądra (Journal of Agribusiness and Rural Development, 2009)
In the paper a concept of farming system in the term of agricultural economics is presented and its usefulness to adopting the new model of rural development on less favoured areas (LFAs) is discussed. Farming system is defined as a holistic description of a farm (or a rural area unit) with respect to agricultural land use (crop and animal production), non-agricultural activities and all determinants of the diverse activities including natural conditions, socio-economic environment, infrastructure and institutions. Evaluation of diversity in farming systems existing on LFAs and their typology is a basis to discuss and arrange most efficient pathways of LFA development and promoting them at the local level. Such an approach to supporting and promoting development of LFAs, being the most sensitive for agricultural and rural policy among rural areas, is specially useful and effective for implementation of concepts, theories and paradigms like sustainable rural development, endogenic development as well as agricultural multifunctionality and diversification of farm activities.